2021
DOI: 10.1093/icvts/ivab109
|View full text |Cite
|
Sign up to set email alerts
|

Does robotic-assisted thymectomy have advantages over video-assisted thymectomy in short-term outcomes? A systematic view and meta-analysis

Abstract: OBJECTIVES A thymic epithelial tumour is the most common primary tumour in the anterior mediastinum of adults. A few retrospective studies compared the short-term outcomes between robotic-assisted thymectomy (RAT) and video-assisted thymectomy (VAT). So, it is necessary to conduct a meta-analysis to further compare these 2 surgical techniques. METHODS EMBASE, Medline and Web of Science were used. Thesaurus terms and medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Many studies have shown superior or equivalent outcomes of minimally invasive mediastinal surgeries in both short-and long-term follow-ups by comparing sternotomy to VATS or RATS and VATS with RATS (1,(5)(6)(7)(8)(9). Our team has also recently demonstrated the safety and feasibility of robotic single-site-assisted thymectomy (4) for reducing the number of incisions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown superior or equivalent outcomes of minimally invasive mediastinal surgeries in both short-and long-term follow-ups by comparing sternotomy to VATS or RATS and VATS with RATS (1,(5)(6)(7)(8)(9). Our team has also recently demonstrated the safety and feasibility of robotic single-site-assisted thymectomy (4) for reducing the number of incisions.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological examination of the thymus following thymectomy has been identified as closely linked to the treatment outcome. Hyperplastic thymus has been associated with a higher rate of complete clinical remission (26,27) . However, in the study conducted by a study (20) , the pathology findings did not correlate with the treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wu [28] compared results of robotic and VATS thymectomies, not identifying significant differences in terms of overall duration of the surgical procedure. O'Sullivan and co‐workers [6] found overall similar outcomes between RATS and VATS, while a more recent contribute [29] highlighted shorter length of stay and reduced complication rate in the RATS subgroup.…”
Section: Commentmentioning
confidence: 98%